Simplify:
x^2 - 2x - 8
x^3 + x^2 - 2x
I factored the numerator into (x+2)(x-4) by doing this:
x^2 - 2x - 8
= x^2 - 4x + 2x -8
= x(x-4)+2(x-4)
= (x+2)(x-4)
Now how would I go about factoring the denominator?
Perhaps, as someone else said, the bottom can have \(\displaystyle x\) factored out, and the top can be factored using the quadratic equation. (On the other hand, top (the quadratic) can also be factored in the traditional manner). Finally, you must cancel out any all common factors to get the final answer.
\(\displaystyle \dfrac{x^{2} - 2x - 8}{x^{3} + x^{2} - 2x}\)
\(\displaystyle \dfrac{(x - 4)(x + 2)}{x(x^{2} + x - 2)}\)
\(\displaystyle \dfrac{(x - 4)(x + 2)}{x(x^{2} + x - 2)}\) - :shock: Careful, another quadratic to factor, on top of the 1st one we did.
\(\displaystyle \dfrac{(x - 4)(x + 2)}{(x + 2)(x - 1)}\) - Cancel out any common factors.... Incorrect - where did the factor 'x' go from the denominator. It should be:
\(\displaystyle \dfrac{(x - 4)(x + 2)}{x*(x + 2)(x - 1)}\)
\(\displaystyle \dfrac{(x - 4)}{x *(x -1)} \ \ [ for \ \ x \ne (-2)]\) - Answer
Finally - step by step on how I factored the quadratics:
a.
\(\displaystyle x^{2} - 2x - 8\) - What two numbers have a product of \(\displaystyle -8\) and a sum of \(\displaystyle 2\)?
\(\displaystyle x^{2} + 2x - 4x - 8\) - Put those two numbers in the middle (while connecting them to x at the same time). In your head, divide the equation into two halves.
\(\displaystyle x(x + 2) - 4(x + 2)\) - Pull out the GCF (greatest common factor) from each side.
\(\displaystyle (x - 4)(x - 2)\)
b.
\(\displaystyle x^{2} - x - 2\)
\(\displaystyle x^{2} - x - 2x - 2\)
\(\displaystyle x(x - 1) + 2(x - 1)\)
Note the above equations can also be solved using the quadratic equation.
Most of the "rest" of what he said was just including the "x" in the denominator. But the crucial part was this: The original fraction was \(\displaystyle \frac{x^2- 2x- 8}{x^3+ x^2- 2x}= \frac{(x- 4)(x+ 2)}{x(x+2)(x- 1)}\) which is clearly NOT DEFINED for x= 0, x= 1 or x= 2. Of course, there is a factor of x+ 2 in both numerator and denominator so we can factor that getting \(\displaystyle \frac{x- 4}{x(x- 1}\). That last fraction is defined for all x except x= 0 and x= 1. Since the first fraction was not defined at x= 2, but this one is, they are NOT equal there. What is true is that \(\displaystyle \frac{x^2- 2x- 8}{x^3+ x^2- 2x}= \frac{x- 4}{x(x- 1)}\) for all x except x= 2. In general, \(\displaystyle \frac{a}{a}= 1\) except for a= 0.
Most of the "rest" of what he said was just including the "x" in the denominator. But the crucial part was this: The original fraction was \(\displaystyle \frac{x^2- 2x- 8}{x^3+ x^2- 2x}= \frac{(x- 4)(x+ 2)}{x(x+2)(x- 1)}\) which is clearly NOT DEFINED for x= 0, x= 1 or x= 2. Of course, there is a factor of x+ 2 in both numerator and denominator so we can factor that getting \(\displaystyle \frac{x- 4}{x(x- 1}\). That last fraction is defined for all x except x= 0 and x= 1. Since the first fraction was not defined at x=-2, but this one is, they are NOT equal there. What is true is that \(\displaystyle \frac{x^2- 2x- 8}{x^3+ x^2- 2x}= \frac{x- 4}{x(x- 1)}\) for all x except x= -2. In general, \(\displaystyle \frac{a}{a}= 1\) except for a= 0.